Pemanfaatan Mesjid Jihadul Umam sebagai Sarana Pembinaan Keagamaan Masyarakat di Desa Muaro Lati Kecamatan Bathin VIII Kabupaten Sarolangun - Imam Haramein; Iis Kartika (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Society is a group of people who form a cultural life; the people. Therefore, they are cultured individuals, and therefore, society needs the best possible guidance and attention. This is not a new problem faced by anyone, not even the state, but rather a long-standing issue. This research was conducted in Muara Lati Village, Bathin VIII District, Sarolangun Regency. This research took the form of descriptive qualitative field research. This study focused on the use of the mosque as a means of community religious development at the Jihadul Umam Mosque in Muara Lati Village, Bathin VIII District, Sarolangun Regency. The primary data used in this research are interview and observation data regarding the use of the mosque as a means of community religious development in Muara Lati Village, Bathin VIII District, Sarolangun Regency, namely: The role of the Jihadul Umam Mosque as a means of community religious development in Muara Lati Village, Bathin VIII District, Sarolangun Regency, Obstacles to the use of the Jihadul Umam Mosque for community religious development in Muara Lati Village, Bathin VIII District, Sarolangun Regency and their solutions. And Efforts to overcome obstacles to the use of the Jihadul Umam Mosque as a means of community religious development in Muara Lati Village, Bathin VIII District, Sarolangun Regency. Besides serving as a center for Islamic worship, the mosque also serves as a center for community development. Among other things, the mosque is used for religious study, education, training, and religious competitions, all of which are usually held inside the mosque. The indigenous population of Muara Lati village is of Malay, Javanese, and Palembang ethnicities. This is consistent with the statement of Mr. Harun, the village head of Muara Lati, who stated: "The indigenous people of Muara Lati village are of Malay ethnicity, followed by people from Java and Palembang”.